Identifying the monasteries and temples with mamba dastan and treasure house, established before the 20th century in Ömnögovi aimag (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
Researchers of traditional Mongolian medicine have been intensively studying the number of Mamba datsan (Medical schools) with treasure houses called Manal jas, Otoch jas, and Mamba jas that existed in Mongolia before the 20th century. In addition, research works have been underway to identify the names of the repressed lama doctors and maarambas since 1937 and to study their biographies and medical works. Within the framework of this research work, we conducted a study for the first time to identify the old Mamba datsan and monasteries with treasure houses of the Manal, Otoch, and Mamba established in Ömnögovi aimag, one of Mongolia’s 21 Aimags. In conducting this study, we first compiled a list of the number of Mamba datsan, treasure houses of the Manal, Otoch, and Mamba of the monasteries and temples established in Ömnögovi aimag. After that, the GPS navigation determines the geographical coordinates of the monasteries and temples also their location in real-time, including latitude and longitude, at the current time. Then, a 1:650000 scale map of the area was drawn and processed. Finally, the map of the monastery with the Mamba datsan, treasure houses of the Manal, Otoch, and Mamba, was taken and verified, and the date of its establishment, description, and the names, biographies, and works of some lama doctors and maarambas who lived in the monastery were clarified. Conclusion: In the territory of present-day Ömnögovi aimag, 22 old monasteries and 24 temples established since the mid 20th century were identified, and a new 1:650,000 scale map of their location was drawn, creating the opportunity to use them in future training and research. Conclusion: In the territory of present-day Ömnögovi aimag, 22 old monasteries and 24 temples established since the mid-20th century were identified, and a new 1:650,000 scale map of their location was drawn, creating the opportunity to use them in future training and research.